PENGGUNAAN PATI SAGU (Metroxylon sp.) SEBAGAI GELLING AGENT TERHADAP KESTABILAN FISIK GEL ASAM SALISILAT - Mansauda, Karlah Lifie Riani; Suoth, Elly Juliana; Rumondor, Erladys M. (Sam Ratulangi University, 2023)
ABSTRACT The gelling agent component is a critical factor that can affect gel’s physical characteristics, such as organoleptic properties, homogeneity, pH, adhesion, and viscosity. Starch is widely use as a filler and binder. The aim of the research was to analyze the effect of the formulation of salicylic acid gel using sago starch as a gelling agent on the physical characteristics of the gel. The research began with the extraction of sago starch, and gel formulations were prepared using starch as the gelling agent with variations in sago starch with F1 (6%), F2 (8%), and F3 (10%). The gels were evaluated for their physical properties, including organoleptic, homogeneity, pH, adhesion, and spreadability testing over a period of 12 weeks at a temperature of 28ºC±2ºC. The research showed that all gel formulations did not undergo changes in organoleptic and homogeneity. In the pH test, all preparations met the requirements. The spreadability test results indicated that all gels did not meet the requirements, while only gel F1 did not meet the adhesion test requirements. Keywords Gelling agent, Sago Starch (Metroxylon sp.), Physical Stability, Gel